Pengaruh Fasilitas dan Kualitas Pelayanan Terhadap Kepuasan Pelanggan Hotel Aston Inn Gideon - Pranata, Ervin Adhitia; Rustam, Triana Ananda (SCIENTIA JOURNAL, 2021)
Facilities and service quality are the main factor that must be considered when the competition is getting tougher, competing hotels promote the best facilities they have to attract customer attention and provide good quality service in order to create customer satisfaction so that customers will be comfortable in the hotel. The purpose of this research is how much influence the facilities and service quality on customer satisfaction at Aston Inn Gideon Hotel with simple random sampling technique, that is data collection was randomly selected from 364 respondents who were distributed using a questionnaire. Quality test of the data in this study using validity test and reliability test, classic assumption test and influence test. In this research using multiple linear regression analysis and analysis of the coefficient of determination (R2), while the hypothesis test in this research used the t test and f test by using the SPSS software version 25. The result of the coefficient of determination (R2) obtained is that the facility and service quality variables have an effect of 84.3% on customer satisfaction.